2019
DOI: 10.1016/j.jhydrol.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Improved reliability of stormwater detention basin performance through water quality data-informed real-time control

Abstract: The objective of stormwater detention basins is to capture stormwater runoff to reduce and delay peak flow and to improve the water quality. These objectives can be improved upon by actively controlling the outflow of the basins rather than traditional passive outflow structures. There are studies demonstrating the performance of the active controls that respond in real-time to basin hydraulics, detention time, and rainfall forecasts. We hypothesize that the performance of these active controls can be improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 64 publications
(88 reference statements)
3
43
0
1
Order By: Relevance
“…Regarding future work, rather than using historical records, considering forecasting information like rainfall forecasts as the FIS optimization inputs to tune CMFPs is valuable for control operation decsision-making (Shishegar et al, 2019). This could facilitate the performance of SWMM_FLC by making the fuzzy control strategy more adaptive to the coming storm events and more resilient to the potential failures (Parolari et al, 2018;Sharior et al, 2019). Although this study has address the downstream flooding problem, future work can switch to water quantity improvement by reducing the pollutant concentration and sedimentation issues in UDSs, especially in some cases with frequent combined sewer overflow and severe illicit intrusions.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Regarding future work, rather than using historical records, considering forecasting information like rainfall forecasts as the FIS optimization inputs to tune CMFPs is valuable for control operation decsision-making (Shishegar et al, 2019). This could facilitate the performance of SWMM_FLC by making the fuzzy control strategy more adaptive to the coming storm events and more resilient to the potential failures (Parolari et al, 2018;Sharior et al, 2019). Although this study has address the downstream flooding problem, future work can switch to water quantity improvement by reducing the pollutant concentration and sedimentation issues in UDSs, especially in some cases with frequent combined sewer overflow and severe illicit intrusions.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…The potential benefits of real‐time control of CSP outlets were demonstrated using a conceptualized CSP modeled in SWMM with a four‐dimensional dynamic system of passive, detention, on/off, and TSS control schemes followed by the use of the Monte Carlo method for failure analysis. The case study, situated in Milwaukee, Wisconsin, USA, showed that TSS control reduced system failure probability compared to on/off and detention control options and that TSS and detention controls settled greater amounts of solids relative to on/off control (Sharior, Mcdonald, & Parolari, 2019). Shishegar, Duchesne, and Pelletier (2019) also explored the use of real‐time control of a CSP outlet via modeling with PCSWMM 7.0.…”
Section: Constructed Stormwater Pondsmentioning
confidence: 99%
“…Detention basins are large-scale devices and are directly connected to urban drainage system. Several results shows that detention basins have good performance avoiding flood downstream, however water quality can be an issue [57]. The detention basin cycle over rainy and dry seasons can accumulate sediments.…”
Section: Detention Basinmentioning
confidence: 99%
“…In order to improve quality performance at detention basins, [57] used RTC algorithms to control a simulated detetion basin. While passive device have shown 64% of TSS removal efficiency, the performance of detention basin with RTC were 95%.…”
Section: Detention Basinmentioning
confidence: 99%